Preparation of rapeseed oil oleogels based on beeswax and its application in beef heart patties to replace animal fat. (September 2021) - Gao, Yanlei; Li, Minghua; Zhang, Li; Wang, Zhuo; Yu, Qunli; Han, Ling
Abstract: This study investigated the effect of beeswax concentration and cooling temperature on the properties of rapeseed oil oleogels, and the effects of using the oleogels to replace 100% beef fat on the physico-chemical and oxidative stability of beef heart patties stored at 4 °C for 14 days. The results indicated that the 10% beeswax oleogel cooled at 4 °C was in a gel state, and it had higher lightness ( L *), melting points, and melting enthalpies than that cooled at 25 °C. Beef heart patties, prepared with the oleogel had a reduction in SFA from 54.08 to 8.34, and an increase in PUFA from 8.88 to 34.37 g/100 g patties. During cold storage, compared with the beef fat patties, the raw oleogel patties had higher moisture and lower fat contents, while the cooked oleogel patties had lower hardness and gumminess values over time. However, in the oleogel patties, the thiobarbituric acid (TBARS), peroxide (POV), and carbonyl values increased until day 14. In conclusion, the oleogel addition improved fatty acid profiles and nutritional index of beef heart patties, but the texture and oxidative stability of patties still need further improvement. Highlights: Beeswax rapeseed oil oleogels were used as fat replacers in beef heart patties. 10% beeswax rapeseed oil oleogels cooled at 4 °C showed high thermal stability. Reformulated beef heart patties were healthier regarding their lipid profile. The oleogels contributed to perform patties with good water retention over time. PCA models discriminated among meat patties according to oleogels and beef fat.